Law and ecology : new environmental foundations - Philippopoulos-Mihalopoulos, Andreas (Routledge, 2011)
Law and Ecology: New Environmental Foundations contains a series of theoretical and applied perspectives on the connection between law and ecology, which together offer a radical and socially responsive foundation for environmental law.
Keywords: Environmental law.; LAW -- Environmental.; Environmental law